The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1807-59322011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis in patients with typical gastroesophageal reflux disease symptoms refractory to proton pump inhibitor

Abstract: BACKGROUND: TREATMEN The contribution of eosinophilic esophagitis (EoE) to refractory gastroesophageal reflux disease (GERD) remains unknown. When EoE and GERD overlap, the clinical, endoscopic and histological findings are nonspecific and cannot be used to distinguish between the two disorders. Limited data are available on this topic, and the interaction between EoE and GERD is a matter of debate.AIM:We have conducted a prospective study of adult patients with refractory GERD to evaluate the overlap of reflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Eosinophilic oesophagitis is increasingly diagnosed in patients with oesophageal symptoms, especially dysphagia and GORD-like symptoms 67 68. The estimated prevalence of eosinophilic oesophagitis based on a multicentre study in Japan was 17.1/100 00069 persons compared with 56.7/100 00070 persons in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Eosinophilic oesophagitis is increasingly diagnosed in patients with oesophageal symptoms, especially dysphagia and GORD-like symptoms 67 68. The estimated prevalence of eosinophilic oesophagitis based on a multicentre study in Japan was 17.1/100 00069 persons compared with 56.7/100 00070 persons in the USA.…”
Section: Resultsmentioning
confidence: 99%
“… 87 90 In one study of 130 patients with persistent heartburn and/or regurgitation despite receiving 6 weeks of omeprazole treatment, only one patient was found to have lesions on upper endoscopy suggestive of EoE. 89 Similarly, a study of 105 patients with PPI-resistant heartburn found that only 0.9% of patients had EoE on upper endoscopy. 90 Overall, EoE is a relatively uncommon disorder and unlikely to be a cause of GERD symptoms that do not respond to PPI therapy.…”
Section: Causes Of Refractory Gerdmentioning
confidence: 99%
“…Other less common symptoms include chest pain, dysphagia, dyspepsia, epigastric pain, nausea, bloating, belching, chronic cough, asthma, laryngitis and other respiratory symptoms[ 45 - 48 ]. Whilst dysphagia is infrequent in GORD, it is the most common presenting symptom for EoE along with food bolus impaction[ 1 , 10 , 49 ]. Approximately 50% of patients who present with food bolus impaction and up to 15% of patients who undergo endoscopy for non-obstructive dysphagia will have EoE[ 6 , 50 ].…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…Fifty to eighty percent of EoE patients have a prior history of atopic symptoms[ 21 ]. Other non-specific symptoms include chest pain, heartburn, regurgitation, dyspepsia, nausea and vomiting, odynophagia, abdominal pain and non-specific throat symptoms[ 1 , 10 , 31 , 33 , 49 , 52 ].…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%